Net-Charge Fluctuations in Pb-Pb Collisions at √sNN=2.76 TeV - Abelev, B.; Adam, J.; Adamova, D.; Adare, A. M.; Aggarwal, M. M.; Rinella, G. Aglieri; Agocs, A. G.; Agostinelli, A.; Aguilar Salazar, S.; Ahammed, Z.; Masoodi, A. Ahmad; Ahmad, N.; et al. (AMER PHYSICAL SOC, 2013)
We report the first measurement of the net-charge fluctuations in Pb-Pb collisions at root s(NN) = 2.76 TeV, measured with the ALICE detector at the CERN Large Hadron Collider. The dynamical fluctuations per unit entropy are observed to decrease when going from peripheral to central collisions. An additional reduction in the amount of fluctuations is seen in comparison to the results from lower energies. We examine the dependence of fluctuations on the pseudorapidity interval, which may account for the dilution of fluctuations during the evolution of the system. We find that the fluctuations at the LHC are smaller compared to the measurements at the BNL Relativistic Heavy Ion Collider, and as such, closer to what has been theoretically predicted for the formation of a quark-gluon plasma. DOI: 10.1103/PhysRevLett.110.152301
Keywords: NUCLEAR COLLISIONS; Physics